Severe Vibrion Vulnificus infection (first case published in Uruguay) - Carrerou, Luis A (Cirugía del Uruguay, 2001)
Report of a clinical case of sepsis due to Vibrio Vulnificus, a pathogen that is little known in our media. Going through the literature it appears to be the first case published in Uruguay. lt should be divulged so that it serve as a reminder of this etiology in the case of patients presenting a picture of cellulitis of lower limbs in phlyctenular form, with or without sepsis, which occurs in summer months and who is suspected of having eaten raw sea food or of having had contact with sea water, al/ the more so in the case of a patient suffering from liver cirrhosis, diabetes or any other cause of inmunodepression. Were this the case the adequate antibiotic therapy should be selected (third generation cephalosporines) as early as possible and the patient should be treat surgically through effective débridement. a